Potentials of campus river re-development towards a performance landscape - Abu Bakar, Aniza; Ibrahim, Putri Haryati (2017)
River forms the fundamental of human survival and is critical for socio-economic development, and healthy ecosystems. It is very imperative in linking the environment and its climate system, and the human society too. Once, river potentials were neglected in a development that it had been not strategically located and to some extent became a dumping area. However, it has been realized that river has high ecological value and can be vibrantly transformed through appropriate development approaches which enhance the physical environment of its surrounding that leads to a positive effect on the economic value, social value, as well as the quality of life. Therefore, this study aims to analyze the potentials of a campus river re-development in creating a performance landscape, whereby the ecological aspects and appropriate technology can be combined to create a great sense of place. Precedence studies of river development and campus development are conducted, followed by site analysis and synthesis which concentrates on the natural environment of the International Islamic University Malaysia (IIUM) river and its surrounding. Potentials of the performance landscape river re-development are analyzed based on the four strands of the eco-infrastructures – green, grey, blue, and red; where they represent the ecological eco-infrastructure, engineering eco-infrastructure, water eco-infrastructure, and human eco-infrastructure respectively. The analysis indicates that the IIUM river and its surroundings have positive potentials to become a performance landscape towards sustainable river re-development.